Breaktrhru [i.e breakthru] Restoration Community Church (Wellington): konteks, identiteit en uitdagings - Mourries, Eben Jacques Philip (Stellenbosch : Stellenbosch University, 2009)
Thesis (MTh)--Stellenbosch University, 2009.